Evaluation of coumarin content and essential oil constituents in Cinnamomum cassia (Nees & T. Nees) J. Presl. - J Rema, A J Jose, N K Leela, T J Zachariah, (Journal of Spices and Aromatic Crops, 2019)
The use of cinnamon bark from commercial sources has raised concerns globally, as it is widely adulterated with Cinnamomum cassia which possesses coumarin that is established as a hepatotoxic chemical in animal trials. The current study reveals the availability of C. cassia trees with high levels of cinnamaldehyde but low in coumarin. The estimated level of coumarin in three trees by HPLC analysis was found to be <100 mg kg-1 of dry bark which is below the stipulated upper levels put forth by the European Food Safety Authority and Food Safety Standards Authority of India. Considering the internationally accepted flavor of cassia oleoresin and the low coumarin levels, the C. cassia of Indian origin can be widely propagated and may be popularized along with C. verum.